Performance on the graded naming test in a population‐based sample of 72‐year‐olds: Associations with life‐course predictors and β‐amyloid pathology: Neuropsychology/Early detection of cognitive decline with neuropsychological tests. (7th December 2020) - Street, Rebecca E.; Lu, Kirsty; Huckvale, Mark; Brotherhood, Emilie V.; Pavisic, Ivanna M.; James, Sarah‐Naomi; Keuss, Sarah E.; Buchanan, Sarah M.; Parker, Thomas D.; Lane, Christopher A.; Keshavan, Ashvini; Murray‐Smith, Heidi; et al.
Abstract: Background: Word‐finding difficulties are a common early feature of Alzheimer's disease (AD) and may be detectable during the preclinical stage. However, the relationship between changes in naming ability and accumulation of β‐amyloid pathology is not fully understood, and questions remain about the role of factors such as sex and education. Method: Participants in Insight 46, a sub‐study of the British 1946 birth cohort, completed baseline cognitive assessments and neuroimaging (combined MRI/ 18 F‐Florbetapir‐PET) at age 69‐71. Follow‐up assessments are currently underway (mean interval 28.9 months, SD 2.1) and include an audio‐recorded version of the 30‐item Graded Naming Test (GNT), which was not administered at baseline. Preliminary interim analyses have been conducted based on 211 cognitively‐normal individuals with complete neuroimaging data (see Table 1 for characteristics). A multivariable regression model was used to investigate predictors of picture naming accuracy, where the outcome was GNT score (max. 30) and predictors were sex, age at follow‐up assessment, β‐amyloid status at baseline (positive / negative), APOE genotype (ε4 carrier/non‐carrier), and prospectively‐collected measures of childhood cognitive ability, education and socioeconomic position (based on occupation). Due to the negatively‐skewed distribution of GNT scores, bootstrapping was used to produce bias‐corrected and accelerated 95% confidence intervals from 2, 000 replications. Results will be updated to include the full sample before the conference. We also plan to include data on naming latency extracted from the audio‐recordings, which may be a more sensitive measure of early changes than naming accuracy. Result: Higher childhood cognitive ability predicted higher GNT scores over 60 years later (Table 2, Figure 1). Men scored 0.9 points higher than women on average. Amyloid‐positive participants scored 1.2 points lower than amyloid‐negative participants on average. These effects were all significant at the 5% level and were mutually independent. Conclusion: Subtle changes in naming accuracy associated with β‐amyloid pathology are detectable in cognitively‐normal individuals as early as age 72. Performance is additionally influenced by sex and general cognitive ability, so these factors should be accounted for where possible in future studies and clinical trials that seek to detect and track the emergence of naming deficits.